Adoption of CSR for Sustainable Development in the Nigerian Banking Sector: An Empirical Study - Ibrahim, Mohammed Gaddafi; Syriac, Nellikunnel Devasia (INTI International University, 2018)
This paper appraises the factors influencing the adoption of Corporate Social Responsibility, (CSR) towards sustainable development in the Nigerian Banking Industry by Exploring Corporate Social Responsibility towards Sustainable development in the Banking Sector in Nigeria. The study reiterates that in relation to the banking sector, CSR is the obligation of banks to manage their social, economic and environmental activities at the local and global level. This involves the banks to consider not only their profitability and growth, but also the interests of society and the environment by taking responsibility for the impact of their activities on stakeholders, employees, shareholders, customers, suppliers and civil society represented by NGOs. This paper examines the perception of the stakeholders on CSR dimensions in the banking sector, dominant CSR activities, issues targeted and potentials of CSR stimulating the sustainability of the banking sector and aims to explore and evaluate the social and ethical practices of the banks in Nigeria, through the perceptions of the Nigerian participants. By doing so, the participant perceptions of the ethical foundations of the banking system were examined, namely the participants’ perception of the banking practices; through the formulation of relevant objectives: This study centres around CSR practices in the banking sector in Nigeria in terms of knowledge and importance of CSR; CSR dimensions; and challenges; determining the relationship between the below factors and CSR in achieving sustainable development; government policy; top management; customer interest, determining which of the factors has greater impacts on banks to adopt CSR as a means of sustainable development; determining how CSR mediates the relationship between the factors that influences it and sustainable development in respect of government policy and top management and customer interest. The paper found that Banks in Nigeria to a large extent is influenced by government policy, customer interest and the bank management on CSR towards sustainable development and concludes that firms engage in CSR mainly for profit maximization.